2014
DOI: 10.1002/jbm.b.33195
|View full text |Cite
|
Sign up to set email alerts
|

Morphology effect of bioglass‐reinforced hydroxyapatite (Bonelike®) on osteoregeneration

Abstract: In the last decades, the well-known disadvantages of autografts and allografts have driven to the development of synthetic bone grafts for bone regeneration. Bonelike(®) , a glass-reinforced hydroxyapatite (HA) composite was developed and registered for bone grafting. This biomaterial is composed by a modified HA matrix, with α- and β-tricalcium phosphate secondary phases. Aiming to improve the biological characteristics of Bonelike(®) , new spherical pelleted granules, of different shape and size, were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…[20][21][22] Specifically, in bone regeneration procedures where synthetic bone grafts are used, an injectable carrier and/or granules stabilizer matrix may ease the clinical application/handling of grafts or drugs, promoting a suitable environment for regeneration. 73 BL is a three-phase material, consisting of αand β-TCP phases homogeneously dispersed in the HAP matrix, resulting in improved mechanical properties and enhanced bioactivity, compared to the commercial HAP. 73 BL is a three-phase material, consisting of αand β-TCP phases homogeneously dispersed in the HAP matrix, resulting in improved mechanical properties and enhanced bioactivity, compared to the commercial HAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Specifically, in bone regeneration procedures where synthetic bone grafts are used, an injectable carrier and/or granules stabilizer matrix may ease the clinical application/handling of grafts or drugs, promoting a suitable environment for regeneration. 73 BL is a three-phase material, consisting of αand β-TCP phases homogeneously dispersed in the HAP matrix, resulting in improved mechanical properties and enhanced bioactivity, compared to the commercial HAP. 73 BL is a three-phase material, consisting of αand β-TCP phases homogeneously dispersed in the HAP matrix, resulting in improved mechanical properties and enhanced bioactivity, compared to the commercial HAP.…”
Section: Discussionmentioning
confidence: 99%
“…9 In this work, HG was combined with glass-reinforced HAP particles (250-500 μm), registered as Bonelike. 73,74 Furthermore, the presence of glass in this formulation allows the introduction of several ions into BL composition, such as magnesium, fluoride, and sodium, making it possible to achieve a chemical composition closer to the mineral phase of the bone. 73,74 Furthermore, the presence of glass in this formulation allows the introduction of several ions into BL composition, such as magnesium, fluoride, and sodium, making it possible to achieve a chemical composition closer to the mineral phase of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…142,207,233,234 Bonelike V R grafts in particulated form have been also successfully employed in several clinical applications, namely in maxillofacial and oral surgery, orthopaedics, and implantology. [235][236][237][238][239][240][241][242][243][244][245] Radiological and histological investigations demonstrated that such composite is highly bioactive, it is rapidly osteointegrated after implantation and it resorbs at a rate that is compatible with the new bone formation. Moreover, Bonelike V R proved to support the adhesion, proliferation, and phenotypic expression of human endothelial cells, therefore it could be a promising candidate for preendothelialization protocols in the bone tissue engineering framework.…”
Section: Phosphate Glass Additionmentioning
confidence: 99%
“…Various synthetic bone substitutes have been developed to overcome these limitations with, to some extent, good clinical effect. Unfortunately, almost all of these substitutes have only been used to refill small cavitary defects in the clinic . In the absence of localized morphogenetic cellular stimuli, the multicellular processes necessary for bone formation cannot be easily induced .…”
Section: Introductionmentioning
confidence: 99%